Real-World Outcomes of Anti-VEGF Treatment for Neovascular Age-Related Macular Degeneration in Turkey: A Multicenter Retrospective Study, Bosphorus Retina Study Group Report No: 1 - Abdullah Özkaya; Levent Karabaş; Cengiz Alagöz; Zeynep Alkın; Özgür Artunay; Selim Bölükbaşı; Gökhan Demir; Mehmet Demir; Ali Demircan; Burak Erden; Gürkan Erdoğan; Mehmet Erdoğan; et al. (Türk Oftalmoloji Dergisi, 2018)
Objectives: To evaluate the real-world outcomes of intravitreal anti-vascular endothelial growth factor (anti-VEGF) treatment in neovascular age-related macular degeneration (nAMD) patients. Materials and Methods: Multicenter, retrospective, interventional, non-comparative study. The records of nAMD patients treated with an anti-VEGF agent on a pro re nata treatment regimen basis between January 2013 and December 2015 were reviewed. The patients who completed a follow-up period of 12 months were included. Primary outcome measures of this study were the visit and injection numbers during the first year. Results: Eight hundred eighty eyes of 783 patients met the inclusion criteria for the study. Mean number of visits at month 12 was 6.9±2.5 (range: 1-15). Mean number of injections at month 12 was 4.1±1.9 (range: 1-11). Mean visual acuity at baseline and months 3, 6, and 12 was 0.90±0.63 LogMAR (range: 0.0-3.0), 0.79±0.57 LogMAR (range: 0.0-3.0), 0.76±0.57 LogMAR (range: 0.0-3.0), and 0.79±0.59 LogMAR (range: 0.0-3.0), respectively. Mean central retinal thickness at baseline and months 6 and 12 was 395±153 μm (range: 91-1582), 330±115 μm (range: 99-975), and 332±114 μm (range: 106-1191), respectively. Conclusion: The numbers of visits and injections were much lower than ideal and were insufficient with the pro re nata treatment regimen.